2011
DOI: 10.1590/s0037-86822011005000008
|View full text |Cite
|
Sign up to set email alerts
|

Infecção por Yersinia pestis, no Estado da Bahia: controle efetivo ou silêncio epidemiológico?

Abstract: These results cannot confirm the eradication of the disease in the entire State, since the cyclic nature of the plague indicates that it can go silent for long periods and then resurge, affecting large numbers of people. Thus, maintenance of active, permanent surveillance is required for early detection and the development of adequate control measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
(17 reference statements)
1
2
0
3
Order By: Relevance
“…The absence of positive results indicate that the transmission cycle in the region is on quiescence, where it is undetectable (Haule et al 2013). A recent study (Saavedra and Dias 2011) reported similar results for a survey performed on rodents, humans and carnivore sentinels. Historically, samples obtained from rodents test negative during periods where no human cases are detected (Almeida et al 1988).…”
Section: Discussionsupporting
confidence: 61%
“…The absence of positive results indicate that the transmission cycle in the region is on quiescence, where it is undetectable (Haule et al 2013). A recent study (Saavedra and Dias 2011) reported similar results for a survey performed on rodents, humans and carnivore sentinels. Historically, samples obtained from rodents test negative during periods where no human cases are detected (Almeida et al 1988).…”
Section: Discussionsupporting
confidence: 61%
“…Distributional data for N. lasiurus and O. nigripes were obtained from speciesLink ( http://splink.cria.org.br ), Global Biodiversity Information Facility ( http://data.gbif.org ) and VertNet ( http://www.vertnet.org ); our searches included the old name of N. lasiurus ( Bolomys lasiurus ). We also consulted various published studies on these rodent species [ 12 - 33 ]. When only textual georeferences were provided we georeferenced them based on two internet resources ( http://www.fallingrain.com/world/ and http:// www.ibge.gov.br/ ).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have been conducted to evaluate the environmental influences in the occurrence of plague in order to better understand the complex cycle of this disease and to predict areas of potential transmission [23][27]. Some of the studies analyzed the relationship between precipitation and temperature with plague, while others looked at altitude, soil, and other conditions [28][30].…”
Section: Introductionmentioning
confidence: 99%